Comparative and Functional Genomics of Legionella Identified Eukaryotic Like Proteins as Key Players in Host–Pathogen Interactions - Gomez-Valero, Laura; Rusniok, Christophe; Cazalet, Christel; Buchrieser, Carmen (Frontiers in Microbiology, 2011)
Although best known for its ability to cause severe pneumonia in people whose immune defenses are weakened, Legionella pneumophila and Legionella longbeachae are two species of a large genus of bacteria that are ubiquitous in nature, where they parasitize protozoa. Adaptation to the host environment and exploitation of host cell functions are critical for the success of these intracellular pathogens. The establishment and publication of the complete genome sequences of L. pneumophila and L. longbeachae isolates paved the way for major breakthroughs in understanding the biology of these organisms. In this review we present the knowledge gained from the analyses and comparison of the complete genome sequences of different L. pneumophila and L. longbeachae strains. Emphasis is given on putative virulence and Legionella life cycle related functions, such as the identification of an extended array of eukaryotic like proteins, many of which have been shown to modulate host cell functions to the pathogen’s advantage. Surprisingly, many of the eukaryotic domain proteins identified in L. pneumophila as well as many substrates of the Dot/Icm type IV secretion system essential for intracellular replication are different between these two species, although they cause the same disease. Finally, evolutionary aspects regarding the eukaryotic like proteins in Legionella are discussed.